Morphological Variations in Tamarindus indica LINN. Fruits and Seed Traits in the Different Agroecological Zones of Uganda - Okello, Jaspher; Okullo, John B. L.; Eilu, Gerald; Nyeko, Philip; Obua, Joseph (International Journal of Ecology, 2018)
An investigation was carried out on variations in the morphological traits of Tamarindus indica LINN. fruits (length, breadth,mass, and pulp mass) and seeds (number and mass) from the different agroecological zones and land use types of Uganda. Fruits were collected from the two land use types in the three agroecological zones and measured for various morphological traits. The study sites were located between 593 and 1,096 meters above sea level. ANOVA was used to test the differences in morphological traits of fruits and seeds between agroecological zones and land use types.The morphological traits relationship was determined using Pearson Correlation Coefficient (R).There were significant (P≤0.05) variations among the T. indica fruits and seed morphological traits within the agroecological zones and land use types. Lake Victoria Crescent agroecological zone recorded higher fruits morphological traits values. Wild and on-farm land use types were superior in fruits and seed traits, respectively. Many seeds per fruit (17) were recorded in Uganda (Eastern agroecological zone) than those recorded elsewhere. Significant uphill positive linear correlations between all morphological traits (P≤0.05) were observed, with the strongest relationships being between seed mass and seed number (R=0.79), fruitmass and fruit length (R=0.75), pulp mass and fruit mass (R=0.73), and seed mass and fruit mass (R=0.73). However, fruit breadth presented slightly weaker positive linear correlations with all other morphological traits. This is the first quantitative evaluation of T. indica morphological traits variation in Uganda. Dispersion/variation and correlation relationships suggest that all the studied morphological traits can be used for selection of plus trees for tree breeding improvement such as yield per tree. The observed variations are probably attributed to influence of agroecological zones’ factors, environmental factors, climate, land use types, and farming systems, a reflection of T. indica adaptation to different conditions showing high genetic and phenotypic differences to be exploited.
Keywords: Morphological; Tamarindus indica LINN; Seed Traits; Agroecological Zones